Localization of a phytochrome-responsive element within the upstream region of pea rbcS-3A. - Gilmartin, P M (1990)
The pea rbcS-3A promoter with a 5' deletion to -166 (-166 rbcS-3A) contains two GT-1-binding sites. Mutational analyses demonstrated that a decrease in affinity for GT-1 correlates with reduced promoter activity. Transcription of -166 rbcS-3A in transgenic etiolated seedlings is induced by red light and suppressed by far-red light, indicating that it contains a phytochrome-responsive element.